O conhecimento de base do profissional de Educação Física do Brasil - Kuhn, Filipy; Nascimento, Juarez Vieira do (2020)
The aim of this study was to highlight the background knowledge of Physical Education professionals (teachers) who work in schools, as well as of professionals who exercise the role of coaches. To this end, a theoretical essay was carried out emphasizing the concepts regarding the theme that involves the knowledge of basic teaching. It was verified that the experiences of teaching practice, feedback (exchange of information) and observations (from colleagues, teachers and/or coaches) were pointed out, both for teachers and coaches, as the experiences that help in the construction of basic knowledge for teaching. It is also noteworthy that there is a body of literature that suggests categories, characteristics and models that sustain this knowledge.
O objetivo do estudo foi destacar o conhecimento de base para os profissionais de Educação Física (professores) que atuam nas escolas, bem como para os profissionais que exercem a função de treinadores. Para tanto, foi realizado um ensaio teórico enfatizando os conceitos a respeito da temática que envolve o conhecimento de base para o ensino. Verificou-se que as experiências de prática docente, os feedback (troca de informações) e as observações (colegas, professores e ou treinadores), foram apontados, tanto para professores como para treinadores, como as experiências que auxiliam na construção do conhecimento de base para o ensino. Destaca-se também que existe um corpo de literatura que sugere categorias, características e modelos que sustentam a base de conhecimento.
Keywords: Physical Education; Background Knowledge; Professional Knowledge; Educação Física^lpt; Conhecimento de base; Conhecimento profissional